Variable radio AGN at high redshift identified in the VLA Sky Survey. Issue Volume 15:Issue S359(2020) (March 2019) - Nyland, Kristina; Dong, Dillon; Patil, Pallavi; Lacy, Mark; Kimball, Amy; Hallinan, Gregg; Sarbadhicary, Sumit; Polisensky, Emil; Kassim, Namir; Peters, Wendy; Clarke, Tracy; Mukherjee, Dipanjan; et al.
Abstract: As part of an on-going study of radio transients in Epoch 1 (2017–2019) of the Very Large Array Sky Survey (VLASS), we have discovered a sample of 0.2 < z < 3.2 active galactic nuclei (AGN) selected in the optical/infrared that have recently brightened dramatically in the radio. These sources would have previously been classified as radio-quiet based on upper limits from the Faint Images of the Radio Sky at Twenty-centimeters (FIRST; 1993-2011) survey; however, they are now consistent with radio-loud quasars. We present a quasi-simultaneous, multi-band (1–18 GHz) VLA follow-up campaign of our sample of AGN with extreme radio variability. We conclude that the radio properties are most consistent with AGN that have recently launched jets within the past few decades, potentially making them among the youngest radio AGN known.